PENGARUH PERSEPSI PEMBELAJARAN DARING TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA FKIP UMMY SOLOK - Rosmiyati Rosmiyati; Roza Zaimil; Reno Warni Pratiwi (STKIP Pesisir Selatan, 2023)
The purpose of this study was to determine whether there is a significant effect of online learning perceptions on the learning outcomes of students of the Mathematics Education Study Program, FKIP UMMY Solok. The approach used is a quantitative approach with a correlational research method. The population in this study were students of the UMMY mathematics education study program in the 2021/2022 academic year. Sampling was carried out using purposive sampling technique. Data collection techniques using questionnaires and documentation. Data analysis techniques in quantitative research use statistics with SPSS 21.0. The results of the study obtained a simple linear regression equation of the effect of perceptions of online learning on learning outcomes, namely Y = 64.814 + 0.264 X. The results of the Fhitung test = 2.296 with a significance level of 0.144> 0.05 so it can be concluded that student perceptions of online learning do not significantly affect learning outcomes. The result of the coefficient of determination (KD) = 9.5% means that the perception of Mathematics Education study program students contributes to learning outcomes by 9.5%. So it can be concluded that the perception of online learning does not significantly affect the learning outcomes of students of the Mathematics Education Study Program, FKIP UMMY Solok.